Peningkatan Skills Berwirausaha Siswa SMA Sullamulmubtadi Anjani Melalui Penerapan Model Experiential Learning Berbasis Kreativitas - Arnila, Riski Ayu; Hilmiyatun, Hilmiyatun (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
Improving entrepreneurial skills by implementing experiential learning models based on creativity is the aims of this research. This is an action research with subject was student of XI grade of Science of SMA Sullamulmubtadi Anjani which is consisting of 23 students. The data were collected by using observation, interview, document analysis and questionnaire methods. They were analyzed by using the quantitative and qualitative methods (mixed methods) tipe convergent parallel mixed methods with side by side comparison model. The results of this research showed that the student’s entrepreneurial skills were increased. Raising the student’s entrepreneurial skills showed by various change in the student’s behavior and skills from various aspects, they are conceptual skill, leadership skill, management skill, technical skill, social skill, selling skill, dan creative. It also characterized by an increasing in the average value of student’s entrepreneurial skills from 66.73 before treatment become 80.92 after treatment in the first cycle and 86.31 in the second cycle. Before treatment only 8.7% students achieved the value above the passing grade score, but after treatment 82,61% students achived the value above the passing grade score.